Analysis of Patient Data Security in Cloud Computing-Based Midwifery Information Systems - Ladjamuddin, Siti Madinah; Al-Bahra, Al-Bahra; Fathiyati, Fathiyati (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2026)
This study aims to analyze patient data security within a cloud-based midwifery information system using the Health and Risk (H&R) approach. While digital transformation in midwifery services enhances the availability and accessibility of patient information, it simultaneously introduces risks regarding confidentiality, integrity, privacy, and unauthorized access to health data. The study employed a descriptive quantitative approach, involving 100 healthcare professionals who use the cloud-based midwifery information system as respondents. Data collection was conducted via a questionnaire covering five security dimensions: confidentiality, integrity, availability, access control, and privacy. Analysis was performed using descriptive statistics and a risk assessment based on a combination of probability and risk impact. The results indicate that the overall level of data security falls into the high category, with a mean score of 3.998. The availability dimension achieved the highest score at 4.18, followed by confidentiality at 4.12 and integrity at 4.05. Meanwhile, access control scored 3.86, and privacy was the lowest-scoring dimension at 3.78. Risk analysis revealed that unauthorized access and data breaches posed the highest risks, each with a risk score of 20. The findings demonstrate that cloud implementation has supported the availability of midwifery information; however, strengthening access controls, privacy protection, authentication, audit trails, encryption, and user security awareness remains essential. This study recommends periodic, risk-based security evaluations to enhance patient data protection and the reliability of the midwifery information system